Development of Mortar Brick Incorporated Dry and Wet Domestic Sludge - Ishak, Nur Izzati (Universiti Teknologi PETRONAS, 2018)
The aims of this research are to evaluate the effect of different percentage of sludge incorporate in mortar. It also done to determine and compare the compressive strength and water absorption of mortar cube with dried sludge and wet sludge incorporate in mortar mix design. With the increases of population, wastewater treatment plant also increases in order to meet the requirement. This will caused sludge produced increases making the environmental quality standard has become more difficult to control and causing problem for environment and social. Many has been researching on how to reduce and reused the amount of sludge produced by the wastewater treatment plant and one of them is to use the sludge as construction material. The dried sludge and wet sledge incorporate into mortar mix replacing sand with the amount of 0%, 5%, 10%, 15%, 20%, and 25% of total weight of sand. Sludge sample was taken from Universiti Teknologi PETRONAS (UTP) wastewater treatment plant. For the dry sludge sample, it was taken from the drying bed. The dry sludge is then grind into smaller grain of 0.75mm of size to before being able to be used in mortar mix design.